Unique and shared risk factors for early childhood victimisation and polyvictimisation in a Brazilian population-based birth cohortResearch in context - Romina Buffarini; Carolina V.N. Coll; Michelle Degli Esposti; Joseph Murray (Elsevier, 2024)
Summary: Background: Identifying modifiable risk factors for child victimisation and polyvictimisation (exposure to multiple types of victimisation) is critical for informing prevention efforts, yet little evidence is available in low- and middle-income countries. The authors aimed to estimate the prevalence of child victimisation and polyvictimisation, and examine unique and shared risk factors in a population-based cohort in Southern Brazil. Methods: Lifetime child victimisation was based on maternal report when children were aged 4 years old (N∼3900) and included five types of victimisation (conventional crime, child maltreatment, peer/sibling victimisation, sexual victimisation, and witnessing/indirect victimisation) and polyvictimisation. Based on a socioecological model, possible risk factors were examined in four levels: community, maternal and family, parent, and child. Findings: Conventional crime and peer/sibling victimisation were the most common types of victimisation (46.0 and 46.5%, respectively), followed by witnessing/indirect victimisation (27.0%), and child maltreatment (11.3%). Sexual victimisation had the lowest prevalence (1.4%). One in 10 (10.1%) children experienced polyvictimisation. In general, boys had higher victimisation rates than girls. There were few risk factors related only to specific types of victimisation (e.g., child disability was uniquely associated with child maltreatment and peer/sibling victimisation). Instead, most risk factors were shared across nearly all victimisation types and also associated with polyvictimisation. These shared risk factors were: violent neighbourhood and low social cohesion, maternal adverse childhood experiences, younger maternal age, parental antisocial behaviour, intimate partner violence against mothers, and maternal depression. Interpretation: These findings reveal a general pattern of accumulative risk effects for different types of victimisation and polyvictimisation, rather than unique risk profiles in children aged four year Prevention efforts should target risk factors at multiple levels (e.g.,: community, maternal and family and parent) during early childhood. Funding: Wellcome Trust grant 10735_Z_18_Z.